Targeting Novel but Less Common Driver Mutations and Chromosomal Translocations in Advanced Non-Small Cell Lung Cancer - Daoud, Alia; Chu, Quincy S. (Frontiers in Oncology, 2017)
Discovery of the epidermal growth factor receptor (EGFR) gene mutation and the anaplastic lymphoma kinase chromosomal translocation in non-small cell lung cancer (NSCLC) has prompted efforts around the world to identify many less common targetable oncogenic drivers. Such concerted efforts have been variably successful in both non-squamous and squamous cell carcinomas of the lung. Some of the targeted therapy for these oncogenic drivers have received regulatory approval for clinical use, while others have modest clinical benefit. In this mini-review, several of these targets will be reviewed.